Analysis of Physical Characteristics of Peat Soil and Peat Land Distribution Based on Laboratory Testing Case Study: South - Southeast Pontianak District - Januar Aristiawan; Dwi Chintya Hanni Pratiwi; Fhebby Cheviakofa; Mohamad Haifan (International Journal of Health Engineering and Technology, 2026)
The existence of peat soil with unfavorable properties has caused several problems that can arise and affect the construction conditions on the soil layer. This unfavorable soil condition is not favorable for civil buildings and if without proper planning will impact the strength and safety of the building. So it is necessary to analyze data using experimental methods in research that begins with investigating soil characteristics at the research location and investigations in the laboratory based on test data in the laboratory for further geotechnical analysis. Classification of peat soil at the research location of South Pontianak and Southeast Pontianak Districts based on test results, can be determined as follows: a. Based on ash content, the peat soil is Medium ash, which is peat soil with ash content between 5% and 15%. b. Based on the absorption level, peat soil is included in the Moderately absorbent and Highly absorbent types, where peat soil can hold 300 – 1500% water. c. Based on the level of maturity (Von Post Classification System), in this study 3 layers of conditions were obtained, namely surface, 50cm and 100cm. In general, for the surface layer, peat soil is classified as sapric, the 50 cm layer is classified as hemic and the 100 cm layer is classified as fibric.